2014
DOI: 10.1177/1753425914524077
|View full text |Cite
|
Sign up to set email alerts
|

Soluble human TLR2 ectodomain binds diacylglycerol from microbial lipopeptides and glycolipids

Abstract: Toll-like receptors (TLRs) are key innate immune receptors that recognize conserved features of biological molecules that are found in microbes. In particular, TLR2 has been reported to be activated by different kinds of microbial ligands. To advance our understanding of the interaction of TLR2 with its ligands, the recombinant human TLR2 ectodomain (hTLR2ED) was expressed using a baculovirus/insect cell expression system, and its biochemical as well as ligand binding properties were investigated. The hTLR2ED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 74 publications
(144 reference statements)
0
25
0
Order By: Relevance
“…TLR2 recognize the broadest range of ligands among TLRs due to its association with other TLRs (TLR1 and TLR6) [15-17]. Crystal structure of TLR2/TLR1 in complex with a triacyl-lipopeptide and TLR2 in complex with a diacyl-lipopeptide showed that the hydrophobic pocket of TLR2 formed by the central LRRs (LRR9 to LRR12) binds the diacylglycerol acyl chains while TLR1 interacts with the N-acyl chains of the ligands ( Figure 1A) [16].…”
Section: Structure and Function/recognition Of Ligands By Tlrsmentioning
confidence: 99%
See 2 more Smart Citations
“…TLR2 recognize the broadest range of ligands among TLRs due to its association with other TLRs (TLR1 and TLR6) [15-17]. Crystal structure of TLR2/TLR1 in complex with a triacyl-lipopeptide and TLR2 in complex with a diacyl-lipopeptide showed that the hydrophobic pocket of TLR2 formed by the central LRRs (LRR9 to LRR12) binds the diacylglycerol acyl chains while TLR1 interacts with the N-acyl chains of the ligands ( Figure 1A) [16].…”
Section: Structure and Function/recognition Of Ligands By Tlrsmentioning
confidence: 99%
“…Crystal structure of TLR2/TLR1 in complex with a triacyl-lipopeptide and TLR2 in complex with a diacyl-lipopeptide showed that the hydrophobic pocket of TLR2 formed by the central LRRs (LRR9 to LRR12) binds the diacylglycerol acyl chains while TLR1 interacts with the N-acyl chains of the ligands ( Figure 1A) [16]. Furthermore, TLR2 also recognize glycolipids such as lipoteichoic acid from Gram-positive bacteria [17, 18], lipoarabinomannan from mycobacteria [17, 19], and GPI anchor structures from Trypanosome Cruzi [20]. We have recently reported that the single hydrophobic pocket of human TLR2 ectodomain is also responsible for binding microbial glycolipids and other lipopeptides [17].…”
Section: Structure and Function/recognition Of Ligands By Tlrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were measured at 680 nm in a CLARIOstar microplate reader (BMG Labtech). Native PAGE experiments were performed to study TLR2-ligand interactions as described (36). Purified human TLR2 (7 μM, final concentration), in some cases preincubated with SSL3ΔN or SSL3ΔN − (40 μM) for 30 min at room temperature, was mixed with Pam 2 CSK 4 Rhodamine (20 μM, InvivoGen) and incubated for 18 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the ligand binding properties of the recombinant human TLR2 ectodomain (hTLR2ED) were investigated (72). It turned out that the ectodomain binds synthetic bacterial and mycoplasmal lipopeptides, S. aureus lipoteichoic acid (obtained from Invivogen, San Diego, CA), and synthetic lipoarabinomannan precursors from Mycobacterium in the absence of its coreceptors TLR1 and TLR6.…”
Section: Lpp In Tlr2-dependent Immune Activationmentioning
confidence: 99%